Factors Influencing Nurses' Performance in Hospital Settings: A Systematic Review - Ni Luh Putu Seriwidhayanti; Elsye Maria Rossa (Indonesian Journal of Global Health Research, 2026)
Nurse performance is a key indicator of healthcare quality in hospitals because it directly relates to patient safety, nursing care effectiveness, and organizational performance. Therefore, a comprehensive synthesis of scientific evidence is needed to understand the determinants of nurse performance in hospital settings. To identify and synthesize scientific evidence related to factors that influence nurse performance in hospitals. This systematic review was prepared following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. A literature search was conducted in PubMed/MEDLINE, Scopus, and CINAHL databases for English-language articles published between 2021 and 2025. A total of 378 articles were identified initially. After removing duplicates and screening titles, abstracts, and full texts based on the PICOS criteria, seven cross-sectional studies met all inclusion criteria. Data were systematically extracted and analyzed using a narrative synthesis approach. The synthesis identified three main categories of factors influencing nurse performance. First, psychological factors and personal capacities, such as self-efficacy, grit, work engagement, and secondary traumatic stress, showed a significant relationship with nurse performance. Second, organizational and practice environment factors, including a supportive work environment, social support, leadership, workload, and reward systems, played a significant role in enhancing or degrading performance. Third, demographic characteristics and physical conditions, such as length of service, education level, health status, and overtime work habits, also influenced nurses' work effectiveness in hospitals. Nurse performance in hospitals is the result of a complex interaction between individual, psychological, and organizational factors. These findings underscore the importance of a holistic approach to nursing management, focusing not only on nurses' clinical competence but also on creating a supportive work environment and organizational policies that are responsive to the needs of the nursing workforce.